2022
DOI: 10.4271/2022-01-0817
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Pedal Misapplication Behavior Using Event Data Recorders

Abstract: <div class="section abstract"><div class="htmlview paragraph">Pedal misapplication (PM) crashes, i.e., crashes caused by a driver pressing one pedal while intending to press another pedal, have historically been identified by searching unstructured crash narratives for keywords and verified via labor-intensive manual inspection. This study proposes an alternative method to identify PM crashes using event data recorders (EDRs). Since drivers in emergency braking situations are motivated to hit the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…In addition to this, Smith et al (2021) further examined the characteristics of crashes resulting from pedal misapplication. This study also reviewed crash descriptions and narratives in the North Carolina state crash database (between 1 st January 2014 and 31 st May 2020) alongside the National Motor Vehicle Crash Causation Survey (NMVCCS) database (between 1 st January 2005 and 31 st December 2007).…”
Section: Crash Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to this, Smith et al (2021) further examined the characteristics of crashes resulting from pedal misapplication. This study also reviewed crash descriptions and narratives in the North Carolina state crash database (between 1 st January 2014 and 31 st May 2020) alongside the National Motor Vehicle Crash Causation Survey (NMVCCS) database (between 1 st January 2005 and 31 st December 2007).…”
Section: Crash Characteristicsmentioning
confidence: 99%
“…Alongside examining crash characteristics, Smith et al (2021) also explored the effect of driver characteristics such as gender on pedal misapplication. The study identified that of the drivers that cause collisions resulting from pedal misapplication, the majority are female.…”
Section: Gender and Staturementioning
confidence: 99%
See 2 more Smart Citations
“…These studies have demonstrated the effect of pedal construction design [ 14 ], age and gender [ 15 , 16 , 17 ], shoe contact area with the pedal, single/dual foot operation mode, foot position [ 18 , 19 ], and driver cognitive function [ 20 , 21 ] on pedal misapplication. Currently, studies on pedal misapplication rely mainly on questionnaire surveys [ 22 ], analysis of vehicle driving data [ 23 ], driver physiological data [ 15 ], video-based foot motion trajectory [ 19 ], and combinations of vehicle driving data and foot posture data [ 12 , 13 , 19 , 20 ]. However, the last three types of data are relatively difficult to acquire during naturalistic driving as they require body posture sensors and medical physiometer devices, which are not usually found in vehicles.…”
Section: Introductionmentioning
confidence: 99%